2022
DOI: 10.3390/bs13010036
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Teacher Career-Related Support Self-Efficacy (TCSSE) Questionnaire

Abstract: Background: Career-related teacher support self-efficacy refers to the teacher’s confidence in his/her own ability to support students’ career choices. To our knowledge, there are neither studies that focus on this topic nor instruments to measure it. Therefore, the current study aimed at developing and validating an instrument to assess teacher career-related support self-efficacy (TCSSE). Methods: In a multi-step process, items were developed and three studies that involved Italian in-service teachers were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A summary version of the tool was then obtained from the independent translations, and back-translated into English by another independent translator whose mother tongue was English to ensure equivalence between the translations. Following this, a sample of 30 participants (15 participants who met the inclusion criteria of the study and 15 participants who were retrieved from the general population) was asked to fill in the pre-final version of the MEC10-IT in order to assess its items’ comprehensibility [ 42 , 43 ]. At this stage, no further adjustment was made ( Table 1 and Appendix A ).…”
Section: Study 1: Factorial Structure Of the Italian Version Of The M...mentioning
confidence: 99%
“…A summary version of the tool was then obtained from the independent translations, and back-translated into English by another independent translator whose mother tongue was English to ensure equivalence between the translations. Following this, a sample of 30 participants (15 participants who met the inclusion criteria of the study and 15 participants who were retrieved from the general population) was asked to fill in the pre-final version of the MEC10-IT in order to assess its items’ comprehensibility [ 42 , 43 ]. At this stage, no further adjustment was made ( Table 1 and Appendix A ).…”
Section: Study 1: Factorial Structure Of the Italian Version Of The M...mentioning
confidence: 99%
“…Second, the study is based on self-reported measures. Though our study tested for the low potential impact of common method bias, future research can benefit from using other data sources, such as teachers’ perceptions or evaluations of their support functions concerning students’ CE behaviours ( Parola et al, 2022 ). This may align with existing research, which has already shown robust evidence reporting positive relationships between the self-reported provision of support and the career development of support receivers (e.g., parents’ self-reported supportive behaviours and their children’s career development, Jiang et al, 2019 ; Liang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a holding environment, schools have the critical function of “scaffolding” student career transitions. Educational systems could help to strengthen and promote career skills, competence, and resources, as well as adolescents' awareness of the choices available and foster students' optimism and hope about their future (Fantinelli et al, 2023 ; Parola et al, 2023 ). Moreover, individuals might be more active in the creation of their careers, in the direction of their active lives, and in choosing the type of role that they have in their society (Fusco et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%